Design & development of collaborative workflow for lean production in a repair & overhaul industry - Wah, T.Y.; Peng, N.H.; Hok, C.S. (2009)
Aerospace fuel nozzles maintenance, repair and overhaul operation is a dynamic process as the workflow is unpredictable. Further detail checking and analyzing on defects are needed in order to determine the workflow. The traditional paper based of work in progress information had been implementing as to manage the nozzles production. However, paper based of work in progress information is inefficient in dealing with these unpredictable and complex workflows. There is a probability of entering or recording the error information when it is in paper based system. This wrong information will cause problem in production line as the results are inconsistent. Furthermore, this inaccurate result will lead to difficulty in tracking the nozzles. Excessive time is needed and wasted in indentifying and correcting the errors. Hence, an electronic based of work in progress system is apparently required as to overcome the shortcoming of the paper based tracking and also to enhance the efficiency of production line. This paper will describe the configurable and customizable work in progress tracking system as a mean to improve over the traditional paper based system.